Botulinum neurotoxin type-A when utilized in animals with trigeminal sensitization induced a antinociceptive effect - Elcio J Piovesan; Michael Oshinsky; Stephen Silberstein; Pedro Andre Kowacs; Edison Matos Novak; Lineu Cesar Werneck (Arquivos de Neuro-Psiquiatria)
ABSTRACT Purpose of the study was evaluate the possible antinociceptive effect of botulinum neurotoxin type-A (BoNT/A) in an experimental model of trigeminal neuralgia. Method Neuropathic pain was induced by surgical constriction of the infraorbital nerve in rats. A control group underwent a sham procedure consisting of surgical exposure of the nerve. Subgroups of each group received either BoNT/A or isotonic saline solution. The clinical response was assessed with the -20°C test. Animals that underwent nerve constriction developed sensitization; the sham group did not. Results The sensitization was reversed by BoNT/A treatment evident 24 hours following application. Pronociceptive effect was observed in the sham group following BoNT/A. Conclusion BoNT/A has an antinociceptive effect in sensitized animals and a pronociceptive effect in non-sensitized animals.